2020
DOI: 10.3390/foods9091237
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Instantized Glycerol Monooleate Ingredient in a Protein-Stabilized Oil-In-Water Emulsion

Abstract: Glycerol monooleate (GMO), casein and whey proteins are surfactants that can stabilize emulsion systems. This study investigates the impact of instantized GMO powders on creaming stability and oxidative stability in protein-stabilized emulsions. Model emulsions with bulk GMO, two instantized GMO powders, and two controls (without GMO) were produced by microfluidization. The droplet size, ζ-potential, viscosity, and creaming index of the emulsions were measured, while oxidative stability was evaluated by analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Prior to analysis, GEO and GEO–vegetable oil (GEO-VO) mixtures (GEO:VO = 1:4) were placed in a 15 mL sample vial for solid-phase microextraction. The headspace solid-phase microextraction was performed to obtain the volatile compounds, referring to Lio et al [ 18 ] and modified slightly. The extraction head was aged at 250 °C for 22 min, and inserted into the top space part of the sample vial.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to analysis, GEO and GEO–vegetable oil (GEO-VO) mixtures (GEO:VO = 1:4) were placed in a 15 mL sample vial for solid-phase microextraction. The headspace solid-phase microextraction was performed to obtain the volatile compounds, referring to Lio et al [ 18 ] and modified slightly. The extraction head was aged at 250 °C for 22 min, and inserted into the top space part of the sample vial.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to being used as an additive in commercial products, 28−30 GMO is also used as a processing aid in the production and stabilization of emulsions and foams in foods. 31,32 The long use history and wide range of applications may result in extremely high levels of GMO in the indoor environment. Both GMO and MO have been detected in natural products, while some other oleate-based chemicals (e.g., BO) can be synthesized from naturally occurring fatty acids.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43,73 In addition, selected chemicals such as GMO have been reported with direct applications as additives in the food industry. 74 This may greatly enhance human exposure, while the potential health risks have not been well explored. Although dermal exposure to semivolatile or volatile organic compounds has received relatively less attention, previous studies have reported that dermal contact may contribute significantly to the total phthalate exposure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations